Fiber optical sensors in biomechanics: research, technology, and applications in mechanical sensing - Roriz, P (2020)
This chapter introduces the use of fiber optic sensors in biomechanics applications. It starts by presenting the field of biomechanics and the technical reasons that make fiber optic sensors an interesting tool for measuring in biomechanics applications. It then explains the application of fiber optic sensors in the biomechanics of rigid bodies, then moves on to deformable bodies, and finishes with fluids, in particular intramuscular and intraarticular pressures. The chapter ends with final remarks about the application of fiber optic sensor technology in biomechanics.